Detecção e caracterização do Parvovírus canino na região metropolitana de Cuiabá, Mato Grosso, Brasil - Fontana, Danúbia de Souza (2012)
The canine parvovirus type 2 (CPV-2) is considered a major cause of infectious diarrhea in dogs less than six months of age. After its emergence in the late 1970s, CPV-2 spread rapidly in across continents, suffering continuous genetic changes that gave rise to new antigenic variants (CPV-2a/b/c). The objective of this study was to detect and genotype CPV-2 by PCR in 50 dogs with clinical, macroscopic and microscopic lesions suggestive of canine parvovirus, sent to the Veterinary Pathology Laboratory UFMT for necropsy. Tissue and fecal samples of these dogs were collected and analyzed by histology and PCR, respectively. Twenty-seven (54%) out of 50 fecal samples collected had specific DNA of CPV-2. Hemorrhagic diarrhea and vomiting were the predominant clinical signs. Histologically, hyperemia and serous rough aspect of the small intestine were the major findings observed, which corresponded microscopically to extensive areas of necrosis and atrophy of intestinal villi. Of the 27 positive samples, 13 (48.1%) were randomly selected and typed by DNA sequence analysis, such as CPV-2c has low genetic variability which some amino acid changes have not yet observed in previous studies. The findings indicate that CPV-2c is the main agent for severe CPV-2 enteritis in dogs necropsied at LPVUFMT.